A six-minute walking test: maximum oxygen consumption in physical education students - Vásquez-Gómez, Jaime (2018)
The Six-Minute Walking Test (SMWT) was completed just in few times in apparently healthy young individuals and university students, while the maximal volume of oxygen consumption (VO2max) prediction has not been taken into consideration. The aim of this study was to elaborate a prediction equation for VO2max from the heart rate recovery (HRR) after completion the SMWT. 127 young in the first stage completed the SMWT and Course Navette Test (CNT), 17 in the second stage (test-retest) completed the SMWT and CNT, and 20 subjects in the third stage completed the SMWT and Bruce test. All physical education students (PES) completions an informed consent. A significant correlation was observed between VO2max estimated trough the CNT and HRR after the SMWT (rho= -0.3; p= 0.001). The correlation between the same variables was r= -0.72 (p= 0.001) in the second stage, and a significant correlation (r= -0.65; p= 0.002) was observed between VO2max directly measured in Bruce test and HRR after the SMWT. From the correlation a prediction equation was elaborated is y= 92.468–(0.278*20-second-HRR) and the standard error of estimation (SEE) was 7.17 ml·kg-1·min-1. The HRR achieved after the SMWT may predict VO2max in PES.